A place called here - Ahern, Cecelia (London : Harper, 2007)
Sandy Shortt has dedicated her life to finding missing people and missing things, so Jack Ruddle enlists her help in searching for his vanished brother. But when Sandy goes missing, Jack must hunt for her--and Sandy must find her way back home from a place called Here--a community where the missing seem to go.
Keywords: Missing persons -- Fiction; Love stories